An Overview of Researches in Chinese BA-structure - Ek-atchariya, Sansanee (Journal of Sinology (วารสารจีนวิทยา), 2013)
This paper aims to present an overview of the study in Chinese BA-structure from the past to the present. It is particularly focused on the studies of the BA-structure since 2000 A.D. onwards, in order to show the current and future research directions on the BA-structure.